Direct and Sensitive Electrochemical Detection of Bisphenol A in Complex Environmental Samples Using a Simple and Convenient Nanochannel-Modified Electrode - Huang, Jie; Zhang, Tongtong; Dong, Guotao; Zhu, Shanshan; Yan, Fei; Liu, Jiyang (Frontiers in Chemistry, 2022)
Rapid, convenient, and sensitive detection of Bisphenol A (BPA), an important endocrine disrupting compound, is crucial for assessing the potential health risks. Electrochemical sensor with simple electrode structure and anti-fouling performance is highly desirable to realize direct analysis of BPA in complex environmental samples without the need for tedious pretreatment. Herein, we present an electrochemical sensing platform using simple nanochannel-modified electrode, which enable direct and sensitive detection of BPA in complex samples. Vertically-ordered mesoporous silica-nanochannel film (VMSF) with high-density nanochannels is rapidly and stably grown on the surface of electrochemically activated glassy carbon electrode (p-GCE) by electrochemically assisted self-assembly (EASA) method. High anti-fouling capability of VMSF/p-GCE sensor is proven by investigating the electrochemical behavior of BPA in the presence of model coexisting interfering molecules including amylum, protein, surfactant and humic acid. The VMSF/p-GCE sensor is able to sensitively detect BPA ranged from 50 nM to 1.0 μM and 1.0 μM to 10.0 μM with low detection limits (14.7 nM). Owing to the electrocatalytic performance and high potential resolution of p-GCE, the sensor exhibits high selectivity for BPA detection in presence of common environmental pollutants including bisphenol S (BPS), catechol (CC), Hydroquinone (HQ), 4-nitrophenol (4-NP). In combination with good anti-fouling of VMSF, direct detection of BPA in environmental water samples and soil leaching solution (SLS) is also realized without separation pretreatment.